Application of the natural deep eutectic solvent choline chloride-sorbitol to extract chlorogenic acid and caffeine from green coffee beans (Coffea canephora) - Erline Yuniarti, Fadlina Chany Saputri, Abdul Mun’im (Journal of Applied Pharmaceutical Science, 2019)
This study aimed to determine the optimum method for extracting caffeine and chlorogenic acid (CGA) from green coffee beans (GCB) of Coffea canephora using choline chloride–sorbitol, a natural deep eutectic solvent (NADES). Three different preparations of choline chloride–sorbitol and choline chloride–sorbitol–urea (2:1, 4:1, and 6:1) were used for the extraction. The most effective preparation was used to evaluate the effect of dilution with water and extraction time. Reverse-phase high-performance liquid chromatography, with a gradient solvent system of 0.1% acetic acid (90%) and acetonitrile (10%), was used to quantify the CGA and caffeine. Choline chloride–sorbitol at a ratio of 4:1 was the most effective for extracting chlorogenic and caffeine, with caffeine and CGA yield of 4.49 and 16.59 mg/g dry weight, respectively. The optimum water concentration was not found. Using a higher NADES dilution for extraction corresponded to an increased yield of caffeine and CGA. The effective time for extraction was found to be 30 minutes, which yielded the most caffeine and CGA. Based on these results, choline chloride–sorbitol could be an alternative green solvent for extracting caffeine and CGA from C. canephora GCB.
Keywords: NADES, Coffea canephora, caffeine, chlorogenic acid, HPLC.